2023
DOI: 10.1186/s12879-023-08294-w
|View full text |Cite
|
Sign up to set email alerts
|

Elevated interleukin (IL)-6 as a predictor of disease severity among Covid-19 patients: a prospective cohort study

Abstract: Background accompanied to the spreading of coronavirus disease 2019 (Covid-19) in the world, identifying factors related to the severity of the disease is one of the interests of physician and medical researchers. We hypothesized that interleukin 6 serum level is associated with severe outcome. Methods In this longitudinal prospective cohort study we enrolled 208 confirmed COVID-19 patients who were admitted to the Tohid Hospital (Sanandaj, Iran). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…6c). These genes were selected as their expression levels have been positively correlated with COVID-19 disease severity and/or they have been proposed as potential targets for prognosis or treatment; SerpinE1 [117], Cxcl10 [118], Nfkb1 [119], IL6 [120], and Hspa1b (a Hsp70 family member) [121, 122].…”
Section: Resultsmentioning
confidence: 99%
“…6c). These genes were selected as their expression levels have been positively correlated with COVID-19 disease severity and/or they have been proposed as potential targets for prognosis or treatment; SerpinE1 [117], Cxcl10 [118], Nfkb1 [119], IL6 [120], and Hspa1b (a Hsp70 family member) [121, 122].…”
Section: Resultsmentioning
confidence: 99%
“…It showed that patients with increased IL-6 levels stayed in the hospital longer and had a higher risk of intensive care unit admission and death compared to patients with lower IL-6 levels. Researchers have suggested that elevated IL-6 levels are associated with worse outcomes in patients with COVID-19, consistent with its role as a potent proinflammatory cytokine and trigger of the cytokine storm in COVID-19 [7].…”
Section: Figure 1 Predictive Value Of Selected Biomarkers For the Sev...mentioning
confidence: 89%
“…IL-6, a pro-inflammatory cytokine, plays a crucial role in the immune response and inflammation. Previous suggestions have implicated its involvement in the severity of COVID-19, with elevated IL-6 levels being associated with a more severe disease course [ 18 , 19 ]. Understanding the genetic factors that influence the severity of COVID-19 disease has clinical implications.…”
Section: Discussionmentioning
confidence: 99%